2018
DOI: 10.1021/acs.jpca.8b02266
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Dynamics of the Metal-to-Ligand Charge Transfer Excited States of Ir(III) Proteo and Deutero Dihydrides

Abstract: For decades, transition metal hydrides have been at the forefront of numerous photocatalytic reactions leveraging either photoacid or photohydride generation. Of upmost importance is the nature of the M-H bond itself, which is typically the major site of photochemical reactivity, particularly in Ir(III) hydrides featuring metal-to-ligand charge transfer (MLCT) excited states. As a departure point for understanding the fundamental spectroscopy and photophysics of the MLCT excited states of Ir(III) diimine hydri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…For example, Fukuzumi and Guldi showed that the 3 MLCT excited state of Ziessel's photocatalyst [Cp*IrH(bipy)] [35] undergoes facile proton transfer to MeOH, [36] while Miller and co‐workers reported photochemical H 2 evolution in MeCN via a photo‐driven disproportionation mechanism [37] . In view of the rich photochemistry of hydride complexes, the scarcity of transient absorption studies is quite surprising [3k,10,36,38,39] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Fukuzumi and Guldi showed that the 3 MLCT excited state of Ziessel's photocatalyst [Cp*IrH(bipy)] [35] undergoes facile proton transfer to MeOH, [36] while Miller and co‐workers reported photochemical H 2 evolution in MeCN via a photo‐driven disproportionation mechanism [37] . In view of the rich photochemistry of hydride complexes, the scarcity of transient absorption studies is quite surprising [3k,10,36,38,39] …”
Section: Resultsmentioning
confidence: 99%
“…[37] In view of the rich photochemistry of hydride complexes, the scarcity of transient absorption studies is quite surprising. [ 3k , 10 , 36 , 38 , 39 ]…”
Section: Resultsmentioning
confidence: 99%
“…In certain cases the mode was verified by preparing the metal deuteride. 7,20,26,36,45,47,52,69,85,88,89,91,104,111,112,121,122,126,132,157,184,201,203,215,217,223 When the hydride is trans to a hydride, usually the antisymmetric H−M−H mode is observed and reported in the region between 1580 and 1900 cm −1 depending on the metal and coligands. The symmetric H−M−H mode at higher wavenumber (1886 cm −1 ) has been located for trans-RuH 2 (C 6 H 5 P-(OC 2 H 5 ) 2 ) 4 by the use of Raman spectroscopy along with the antisymmetric IR-active mode at 1643 cm −1 .…”
Section: ■ Methodology and Resultsmentioning
confidence: 99%
“…This provides the basis for the further investigation of ultrafast photoinduced dynamics in other solvents as well as in the gas phase . Note, that reports on ultrafast processes in transition‐metal complexes, and especially on multinuclear metal hydrides, remain rather scarce . Moreover, we will pursue the subject of silver hydride luminescence further, because it plays a major role in the design and application of atomically precise nanoclusters …”
Section: Resultsmentioning
confidence: 85%
“…Our combined experimental and theoretical results hence provide a basis for further detailed spectroscopic and ultrafast dynamics investigations, specifically for studying metal–metal interactions under electronic excitation and identification of hydride charge‐transfer processes. The dynamics of the latter are largely unexplored, but present essential relaxation steps in electronically excited metal hydrides and are decisive for their photochemistry. Moreover, we believe that they could also be utilized to gain a mechanistic understanding and control of the growth of metal nanoclusters and hydrides.…”
Section: Discussionmentioning
confidence: 99%